Interação entre fontes nitrogenadas e plantas de cobertura de outono/inverno: impacto no desempenho agronômico de trigo e na diversidade da fauna edáfica - Soares, Eveline Ferreira (2022)
Information regarding the use of ground cover plants in autumn/winter, with the use of poultry litter as a source of nitrogen (N) in wheat, is scarce and the studies, in most cases, are quite segmented. With the rise in the prices of mineral nitrogen fertilizers and the prospect of a lack of inputs for the next harvest, it is necessary to think of strategies capable of mitigating possible impacts. Thus, the objective of this study was to determine the contribution of isolated and/or intercropped cultivation of ground cover plants in autumn/winter and the use of poultry litter as a source of N in the wheat crop in succession on the mesofauna and macrofauna soil community, plant parameters and final wheat grain yield. The study was conducted in the 2019 and 2020 crop years in a Distroferric Red Latosol, at the Federal University of Santa Maria campus of Frederico Westphalen, in a randomized block design with split plots and three replications. The treatments, in the plots, consisted of the autumn/winter ground cover crops: black oat, forage turnip, black oat + forage turnip intercropping and fallow (without cover plants). In the subplots, the treatments consisted of four N management strategies in the wheat crop: 100% of N recommendation via mineral source (urea), 100% of N via poultry litter, 50% of N via poultry litter + 50% of N via mineral and the treatment control (without N application). The application of poultry litter increased the productivity of wheat grains, being an alternative for partial replacement when associated with urea, or in total replacement of N-mineral. For treatments with ground cover plants, single forage turnip crops and the intercropping of black oat + forage turnip positively influenced the agronomic performance and wheat grain yield. For the edaphic fauna, the use of ground cover plants in autumn/winter induced the abundance of organisms that were represented mostly by the order Collembola, belonging to the Entomobryidae family. The isolated or intercropped cultivation of ground cover plants, associated with the use of N via poultry litter, allowed a greater diversity of species and a more stable distribution in the community of edaphic organisms.